Joe and Sparky, Party Animals! - Michalak, Jamie (Somerville, Massachusetts Candlewick Press, 2017)
The endearingly mismatched duo has their hands full when a party for a friend goes comically awry. One day Joe, an exuberant giraffe, hears a commotion coming from another part of the famous cageless zoo he calls home. Joined by his small, green, slightly more serious turtle friend, Sparky, Joe discovers the source of the hullabaloo: a group of children - or noisy short people, as Joe and Sparky call them - having a party. Inspired, Joe decides to throw a party for his pet worm, Wiggy. Theres just one problem: Sparky is not entirely sure if Wiggy even exists! What will happen when every animal in the zoo shows up to Wiggys party with presents and cake? Worm or no worm, this silly, satisfying tale is sure to leave new readers smiling.
Keywords: Zoos -- Juvenile fiction; Animals -- Juvenile fiction; Parties -- Juvenile fiction; Zoos -- Fiction; Animals -- Fiction; Parties -- Fiction; Zoos -- Fiction; Animals -- Fiction; Parties -- Fiction